2022
DOI: 10.31219/osf.io/fma57
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rethinking the “gypsy” retrotransposon: A roadmap for community-driven reconsideration of problematic gene names

Abstract: Transposable elements (TE) can replicate and mobilize at the detriment of the host genome they reside in; thus, they are considered selfish or parasitic genetic elements. First discovered in Drosophila, the gypsy retroelement was named in reference to the migratory history of the Romani people. This name later came to denote an entire family of wide-spread TEs and related viruses. Here, we discuss why the continued use of “gypsy” in this scientific context is insensitive and perpetuates racial stereotypes. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…The name we used throughout the paper for each element is shown, along with its original name in RepBase ( 21) fngrep version 25.10, the class, and the family each element belongs to. We adopted a naming convention for Ty3 (formerly Gypsy) elements, where any "GY" in the RepBase name was replaced with "Ty3" in order to use a non-discriminatory and respectful naming scheme (56). Grasshopper is the original name of the GYPSY1 RepBase element, so it is used instead (57).…”
Section: Effector Annotation and Analysismentioning
confidence: 99%
“…The name we used throughout the paper for each element is shown, along with its original name in RepBase ( 21) fngrep version 25.10, the class, and the family each element belongs to. We adopted a naming convention for Ty3 (formerly Gypsy) elements, where any "GY" in the RepBase name was replaced with "Ty3" in order to use a non-discriminatory and respectful naming scheme (56). Grasshopper is the original name of the GYPSY1 RepBase element, so it is used instead (57).…”
Section: Effector Annotation and Analysismentioning
confidence: 99%
“…At the whole-genome scale, Microbotryum lychnidis-dioicae carries long-terminal repeat (LTR) retroelements from the Copia and Ty3 (also known as Gypsy, but see Wei et al, 2022) superfamilies (Hood et al, 2005;Amselem et al, 2015) as well as, to a lesser extent, Helitron DNA transposons, i.e., rolling-circle replicating TEs (Kapitonov & Jurka, 2001). In the Microbotryum species parasitizing Dianthus carthusianorum, a burst of Ty3 retroelements has caused a massive accumulation of this element in a short period of time, in spite of RIP-like activity (Horns et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…At the whole-genome scale, Microbotryum lychnidis-dioicae carries long-terminal repeat (LTR) retroelements from the Copia and Ty3 (also known as Gypsy , but see Wei et al ., 2022) superfamilies (Hood et al ., 2005; Amselem et al ., 2015) as well as, to a lesser extent, Helitron DNA transposons, i.e. , rolling-circle replicating TEs (Kapitonov & Jurka, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…5E and S18). In particular, the DEG ~ Field:Population group was highly enriched for Ty3 (also known as Gypsy , Wei et al, 2022) retrotransposons in the J3 population ( P = 1.3 × 10 −6 , Fisher’s exact test). We also found that non-CG DMGs were TE insertion hotspots (Fig 5E), suggesting that many of the methylation changes may have arisen as a result of TE methylation spreading to genic regions.…”
Section: Resultsmentioning
confidence: 99%